Ferronematics based on the nematic 6CB in combined electric and magnetic fields. (3rd August 2017) - Gdovinová, V.; Tomašovičová, N.; Éber, N.; Salamon, P.; Tóth-Katona, T.; Závišová, V.; Kováč, J.; Jadżyn, J.; Kopčanský, P.
ABSTRACT: This work is devoted to the study of composite systems of the liquid crystal 4- n -hexyl-4-cyanobiphenyl (6CB) doped with differently shaped magnetite nanoparticles. The ferronematic samples were prepared with the volume concentration ofφ =10 - 5 of spherical, as well as of rod-like magnetic particles. The structural transitions in ferronematic samples were observed by capacitance measurements in a capacitor made of indium-tin-oxide-coated glass electrodes in combined electric and magnetic fields.